Assessing the role of sodium fluorescein in peripheral nerve sheath tumors and mimicking lesions surgery: An update after 142 cases - Nazzi, Vittoria; Innocenti, Niccolò; Castelli, Nicolò; Tramacere, Irene; Eoli, Marica; Cojazzi, Vittoria; Gatti, Laura; Acerbi, Francesco; Falco, Jacopo; Vetrano, Ignazio G. (Frontiers in Oncology, 2023)
Objective: Peripheral nerve sheath tumors (PNST) include mainly schwannomas and neurofibromas. Surgical resection represents the mainstay of treatment but due to their pathogenesis, distinguishing between intact functional nerve and the fibers from whence the PNST arose may not always be easy to perform, constituting the most relevant risk factor in determining a worsening in neurological condition. The introduction of intraoperative tools to better visualize these tumors could help achieve a gross-total resection. In this study, we analyzed the effect of sodium fluorescein (SF) on the visualization and resection of a large cohort of PNST. Methods: Between September 2018 and December 2021, 142 consecutive patients harboring a suspected PNST underwent fluorescein-guided surgery at the Department of Neurosurgery of the Fondazione IRCCS Istituto Neurologico Carlo Besta, Milan, Italy. All patients presented with a different degree of contrast enhancement at pre-operative MRI. SF was intravenously injected after intubation at 1 mg/kg. Intraoperative fluorescein characteristics and postoperative neurological and radiological outcomes were collected, analyzed, and retrospectively compared with a historical series. Results: 142 patients were included (42 syndromic and 100 sporadic); schwannoma was the predominant histology, followed by neurofibroma (17 neurofibroma e 12 plexiform neurofibroma) and MPNST. Bright fluorescence was present in all cases of schwannomas and neurofibromas, although with a less homogeneous pattern, whereas it was significantly less evident for malignant PNST; perineurioma and hybrid nerve sheath tumors were characterized by a faint fluorescence enhancement. The surgical resection rate in the general population and even among the subgroups was about 66.7%; from the comparative analysis, we found a consistently higher rate of complete tumor removal in plexiform neurofibromas, 66% in the "fluorescent" group vs 44% in the "historical" group (p-value < 0.05). The rate of complications and mean surgical time were superimposable among the two populations. Conclusions: SF is a valuable method for safe fluorescence-guided PNST resection. Our data showed a positive effect of fluorescein-guided surgery in increasing the rate of surgical resection of plexiform neurofibromas, suggesting a possible role in improving the functional and oncological outcome of these lesions.